Mecânica quântica supersimétrica: aplicações - Balaños Coral, Jonathan [UNESP] (2013)
From the concepts of supersymmetric quantum mechanics (SUSYQM)we studied the hydrogen atom and the three-dimensional harmonic oscillator in non-relativistic and relativistic levels . The calculation of eigenenergies and eigenfunctions of such systems were also performed by the conventional method in order to establish a comparison with the results obtained from SUSYQM